Food-based social entrepreneur mindset: a review and research direction - Sabri, Khairun Najihah; Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah; Ali @ Hamid, Mass Hareeza; Ghazali, Hazrina (Human Resource Management Academic Research Society, 2021)
There is a rising trend of social entrepreneurial activities in Malaysia, but the research on social entrepreneurship, particularly within the context of food-based social entrepreneurs and mindset, is limited. This paper examines the components of mindset among food-based social entrepreneurship in Malaysia. A detailed review is used to sort out the literature and develop the research direction of the study. The review is focused on components of mindset among social entrepreneurs. An entrepreneurial mindset could sharpen the focus and strengthen the rationale compared to merely entrepreneurial competencies. However, research on the entrepreneurial mindset does not address these particularities, and the entrepreneur mindset attributes have been investigated mainly within the commercial entrepreneurial context. As the demand for food is continuously increasing, there are plenty of rooms to grow, to explore and understand the components that underlie the food-based social entrepreneurs' mindset. This paper is anticipated to shed some light on society and policymakers, which later help develop social entrepreneurship in Malaysia.